Unusual Diseases with Common Symptoms A Clinical Casebook (Springer International Publishing, 2018)
This book presents detailed case reports of unusual diseases with common symptoms, many of which have emerged in the past decade as a result of nature, advances in medical treatment, and increasing recognition of specific underpinnings of human biology and immunology. These rare diseases must now be considered when the mundane diagnoses do not exactly fit the patient's clinical history or treatment fails. Some of these diseases include: eosinophilic esophagitis, blastocystis hominis infection, and paromyces allergic fungal sinusitis. Chapters provide in depth clinical examples of a wide range of diseases affecting multiple organ systems. Each case is structured by: a vignette of the case, background / salient features of the case, diagnosis, treatment, key points, and questions to aid in critical thinking. Unusual Diseases with Common Symptoms: A Clinical Casebook is of great interest to practicing physicians and as a teaching resource for students and residents who will one day encounter conditions more complex than they initially appear.